Causes analysis of red tide event in the offshore sea of Rongcheng, Shandong Province, China based on a coupled physical-biological model - Jiang, Wenxin; Liu, Changhua; Yang, Dezhou; Xu, Lingjing; Yin, Baoshu (Frontiers in Marine Science, 2024)
The abnormal reduction of kelp production occurred in Rongcheng area of the Yellow Sea in 2021, which is closely related to the red tide. However, the relationship between the red tide event and the hydrodynamic environment remains unclear. In response to these issues, this study established a coupled physical-biological model which coupling the ROMS dynamic model with the RED_TIDE biological model for the Yellow Sea and Bohai Sea region, and discussed driving factors of this red tide. Based on this coupled model, various factors influencing the development of red tide were investigated, with a focus on analyzing the key factors contributing to the occurrence of the red tide event in the northern sea area of the Shandong Peninsula in 2021. The aggregation of dinoflagellate cells triggers red tide events. The distribution characteristics and concentration changes of dinoflagellate cells were studied by designing simulation experiments under different conditions to reflect the contributions of various influencing factors to red tide. According to observation data and simulation experiments, this study explored the effects of factors such as light conditions, tides, Yellow River runoff and wind field on the distribution and concentration of dinoflagellate cells. The variation of wind field can promote the proliferation and aggregation of dinoflagellate cells, serving as key factors in triggering red tide. The occurrence of red tide is a complex ecological phenomenon influenced by multiple factors, necessitating the comprehensive consideration of these factors to more accurately predict and prevent red tide events.